2021
DOI: 10.3390/ijerph18062978
|View full text |Cite
|
Sign up to set email alerts
|

Ego-Resiliency and Perceived Social Support in Late Childhood: A Latent Growth Modeling Approach

Abstract: This study explored the change trajectory of schoolchildren’s ego-resiliency and perceived social support and investigated the effect of perceived social support on ego-resiliency across four time points. A sample of 437 children aged 8–13 years (M = 10.99, SD = 0.70, 51.5% boys) completed assessments at four time points. The results indicated that ego-resiliency showed an increasing linear trend and perceived social support showed a declining linear trend. Perceived social support had a positive effect on ego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…These findings are similar to the findings reported on healthy and unhealthy individuals showing that resilience may foster social support [4] . Indeed, there is a reciprocal relationship between resilience and social support [29,32] . That is, a high level of perceived social support may help individuals to gain more confidence in coping with difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to the findings reported on healthy and unhealthy individuals showing that resilience may foster social support [4] . Indeed, there is a reciprocal relationship between resilience and social support [29,32] . That is, a high level of perceived social support may help individuals to gain more confidence in coping with difficulties.…”
Section: Discussionmentioning
confidence: 99%
“… 15 However, according to some more modern approaches, resilience can be defined as a process that facilitates adaptation. Recently, research has been conducted using a relatively new scale to determine ego-resiliency, 16 which has not yet been fully explored. In Block’s concept, ego-resiliency is related to the ability to flexibly adapt to the stimuli coming from the changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…This statistical analysis method is rather novel in the research on orthopaedic care. A recent study from Bitar et al (2020) using this approach explored trajectories of physical activity in osteoarthritis patients with a 5‐year follow‐up, and the approach has been shown to be useful and valid for exploring the trajectories of developmental psychology, such as the investigation of ego‐resilience in childhood (Chen et al, 2021) and grief after the death of a significant person (Smith & Ehlers, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…knee arthroplasty, latent class growth modelling, longitudinal studies, nursing, predictors, psychological resilience, trajectory approach has been shown to be useful and valid for exploring the trajectories of developmental psychology, such as the investigation of ego-resilience in childhood (Chen et al, 2021) and grief after the death of a significant person (Smith & Ehlers, 2020).…”
Section: Introductionmentioning
confidence: 99%